PASHTUN IMAGES IN CONTEMPORARY PAKISTANI FICTION IN ENGLISH - Syed Hanif Rasool (University of Chitral Journal of Linguistics and Literature, 2025)
Living in an area that has long been a battlefield where various world powers haveoften been at loggerheads, Pashtuns have frequently drawn the attention of severalworks of fiction. Yet literary scholars have largely ignored the importance of theseworks of fiction looking into the lives of Pashtuns. This paper proposes that fromthe times of the Cold War to those of the War on Terror, Pashtun identities havebeen clouded by the hegemonic discourses of the contesting global powers, leadingto gaps and silences in their depiction in literature.This paper argues that thePashtun images in contemporary Pakistani fiction in English exhibit stronginfluences of the dominating narratives; simultaneously, however, they seem tooffer various patterns of subversion of the prevailing power narratives. Despite thefact that Pashtuns are generally regarded as the most subversive people of SouthAsia and that their lands have been regarded significant strategically as well asgeographically, yet they are portrayed as the Others of the mainstream culturaldiscourses. This paper aims to highlight the contours of the socio-cultural andpolitical valuation of Pashtuns in contemporary Pakistani fiction in English.